Education as the Essential Part of Public Relations Ethics Codes - Matilda Kolić Stanić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The end of the twentieth century and the beginning of the 21st century were characterized by increase in faculties and in public relations associations. For members of PR-associations, professional activities are regulated by ethics codes. The goal of this paper is to explore which place in the ethics codes of public relations associations takes the importance of education and how different associations in different countries consider education as professional duty of PR-experts. This paper provides a qualitative analysis of the content of 13 ethical codes; 2 international and 11 national professional associations active in 7 countries: Austria, Germany, Croatia, Italy, Spain, United Kingdom and Unites States. The analysis had revealed that the majority of analysed codes does not consider the education as the essential duty of public relations professionals, although some of them emphasized the positive connection of education and ethical conduct.
Keywords: I21; M14; 330; communications; public relations; ethics; codes; education; associations